The Enhanced Immune Protection in Chinese Mitten Crab Eriocheir sinensis Against the Second Exposure to Bacteria Aeromonas hydrophila - Wang, Jingjing; Yang, Bin; Wang, Weilin; Song, Xiaorui; Jiang, Qiufen; Qiu, Limei; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2019)
Accumulating evidences suggest that the enhanced immune responses and increased protection against bacteria-induced mortality can be initiated after the primary exposure to various microbial communities and their components in invertebrates. In the present study, the survival rate and immune responses of Chinese mitten crab Eriocheir sinensis were determined after an immune priming (IP) with formalin-killed Aeromonas hydrophila and an immune challenge (ICH) with the same but live pathogen (Ah group). A group in which the animals received a salt injection prior to challenge was maintained as control (Ns group). In the present study, it was shown that an IP with killed A. hydrophila can significantly protect the crabs against the ICH with a lethal dose of the live pathogen. The increased survival was associated with elevated rate and duration of phagocytosis. The antibacterial activity of the serum was significantly increased in Ah group compared to that in Ns group. Significant changes of phenoloxidase (PO) activities were also found between Ah and Ns group but not in Ah group between IP and ICH. No significant changes of lysozyme were found in Ah and NS group during the whole experiment except 3 h after IP. In addition, the levels of transcripts and protein of Dscam were increased in hemocytes of the crabs from Ah group. All the results suggested that a primary immune priming with a particular killed pathogen could induce an enhanced immunity in crabs when they were encountered secondly with the same live pathogen. The evidences of elevated immune protections in crabs would contribute to better understand the mechanism of immune priming in invertebrates.